Poverty and Women Status among the Fishers Community in Contemporary Era - Waskito Widi Wardojo (Diponegoro University, 2019)
There is a significant change in how people see fishers these days, as previously this particular profession was tightly related to poverty, and had the tendency to be subsistence. This includes the role of female fishers. Now they do not necessarily have to stay at home waiting for the return of their husband from fishing, but actually, participate in the act of fishing on the sea along with their husband. Today, women already acknowledged by the government. There is even a success story of female fishers in Juwana, Pati, Central Java. In the eighties, fishers in that area lived in poverty. Now they thrive and leading life in prosperity. Does this mean poverty is not so tightly related to the fishers anymore? How fishers of Juwana answer the question? How is the fate of female fishers now that their status is already acknowledged as a legit profession?